North Atlantic TC size and storm tide reconstructions, 1950-2020 ... - Gori, Avantika; Lin, Ning (Designsafe-CI, 2023)
North Atlantic tropical cyclone size (outer size and radius of maximum winds) and storm tide reconstructions from 1950-2020. The reconstruction method utilizes ERA5 reanalysis data to estimate TC outer size and the complete wind profile of Chavas et al. (2015) (CLE15) to estimate TC Rmax. Then storm tides are reconstructed based on estimate sizes, Best Track information, and the hydrodynamic model ADCIRC. See Gori et al. (2023) [DOI to be added] for details. ...